2017
DOI: 10.1007/s10528-017-9806-9
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Relationship Between Oral Squamous Cell Carcinoma and DNA Repair Genes

Abstract: Single nucleotide polymorphisms of DNA repair genes alter protein function and modulate DNA repair efficiency in various cancers. The X-ray repair cross-complementing group (XRCC) is responsible for the repair of DNA base damage and single-strand breaks. The aim of our study was to investigate the association of XRCC1 Arg399Gln and XRCC3 Thr241Met polymorphisms with the susceptibility to develop oral squamous cell carcinoma (OSCC) in Turkish subjects. One hundred eleven patients with OSCC and 148 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…8 Carcinogenic agents can trigger the accumulation of genetic alterations, including changes in the normal functions of proto-oncogenes and tumor suppressor genes that affect the cell cycle, immunity and cell differentiation, proliferation and death, as well as modifications in DNA repair. 11,12,13 The DNA repair system plays a fundamental role in the protection of the genome against endogenous and exogenous agents, preventing cells altered by carcinogens from continuing the cell cycle and their inappropriate proliferation. 13,14 DNA repair proteins play an important role in different pathways involved in the maintenance of DNA structure and function and might be associated with the clinical prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Carcinogenic agents can trigger the accumulation of genetic alterations, including changes in the normal functions of proto-oncogenes and tumor suppressor genes that affect the cell cycle, immunity and cell differentiation, proliferation and death, as well as modifications in DNA repair. 11,12,13 The DNA repair system plays a fundamental role in the protection of the genome against endogenous and exogenous agents, preventing cells altered by carcinogens from continuing the cell cycle and their inappropriate proliferation. 13,14 DNA repair proteins play an important role in different pathways involved in the maintenance of DNA structure and function and might be associated with the clinical prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,13 The DNA repair system plays a fundamental role in the protection of the genome against endogenous and exogenous agents, preventing cells altered by carcinogens from continuing the cell cycle and their inappropriate proliferation. 13,14 DNA repair proteins play an important role in different pathways involved in the maintenance of DNA structure and function and might be associated with the clinical prognosis of patients. 13,15 Human X-ray repair cross-complementing 1 (XRCC1) is the first mammalian DNA repair gene isolated that affects cell sensitivity to ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variant rs861539 in XRCC3 , characterized by a C–T transversion at position 722, affects protein repair function, leading to genetic instability and DNA DSB accumulation (Lindh, Rafii, Schultz, Cox, & Helleday, ; Matullo et al, ; Nowacka‐Zawisza et al, ; Pierce, Johnson, Thompson, & Jasin, ). Previous studies have demonstrated that these genetic variants in RAD51 and XRCC3 contribute to development and progression in acute myeloid leukemia and carcinomas in several locations (Avci, Ergen, Bireller, Ertugrul, & Cakmakoglu, ; Dos Reis et al, ; Farnebo et al, ; Flores‐Obando, Gollin, & Ragin, ). However, their role in oral and oropharyngeal SCC is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Na fisiopatologia do CEO, biomarcadores como: tamanho do tumor, grau histológico, estágio da doença, hábitos orais e variantes genéticas podem exercer impacto no prognóstico e tratamento dos pacientes. Genes responsáveis pelo reparo do DNA são essenciais na prevenção da tumorigênese (Avci et al, 2017). Estima-se que cerca de 50.000 a 500.000 agressões ocorrem ao DNA diariamente como resultado metabólico do nosso organismo.…”
Section: Carcinoma Epidermóide Oral (Ceo)unclassified